2017
DOI: 10.1097/gox.0000000000001258
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin and the Breast Implant Capsule

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
4
2
Order By: Relevance
“…Our data now show that serum concentration levels of Activin A and follistatin in patients with capsular contracture differ from the standard serum level determined by us and the values that occur in long-term patients asymptomatic with regard to capsular contracture. 34,35 Contrary to Dohi et al and Frenkiel et al 25,36 , we could not observe that higher follistatin concentrations were also associated with higher Activin A concentrations. We observed normal Activin A serum levels and below standard follistatin levels in capsular fibrosis patients.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our data now show that serum concentration levels of Activin A and follistatin in patients with capsular contracture differ from the standard serum level determined by us and the values that occur in long-term patients asymptomatic with regard to capsular contracture. 34,35 Contrary to Dohi et al and Frenkiel et al 25,36 , we could not observe that higher follistatin concentrations were also associated with higher Activin A concentrations. We observed normal Activin A serum levels and below standard follistatin levels in capsular fibrosis patients.…”
Section: Discussioncontrasting
confidence: 95%
“…This assumption is confirmed in the animal experiments with regard to capsular fibrosis as a pathological fibrotic process, where it could be demonstrated that the local application of follistatin in the implant pocket led to a significant reduction in pericapsular inflammation and fibrosis. 25 The aim of this study was to determine whether and how the serum concentrations of Activin A and follistatin changes after breast augmentation with silicone implants. This is intended to provide insights into the possible influence of the activin-follistatin axis in the development of the capsular contracture.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of breast prosthetic implant-associated SCC is not clear. Metaplastic squamous epithelialization of the capsular lining or entrapment of skin or adnexal elements has been acknowledged [15]. The most common histological characterization in implant capsules was collagen bre alignment and brous capsule [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Prepared breast implant surface materials were seeded into 8-week old Balb/c female mice (weight ~20 g, Jackson Laboratory), according to a published paper (25). Mice were maintained in the specific-pathogen-free environment (control at constant 23°C and 40–60% humidity) with a 12-h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%